SKU performance and distribution: A large-scale analysis of the role of product characteristics with store scanner data. (July 2021) - Hirche, Martin; Greenacre, Luke; Nenycz-Thiel, Magda; Loose, Simone; Lockshin, Larry
Abstract: This study investigates the relationship between distribution and market share across various consumer packaged goods (CPG) categories and specific stock keeping units (SKUs). The study identifies product-related characteristics that result in substantive deviations above or below market shares predicted by the distribution – market share relationship. The association of product price, brand (private label [PL] v. national brand [NB]) and pack size with above (or below) expected market share for a given distribution level is analysed. Results indicate larger pack sizes, PL and medium price levels result in market share above what would be predicted by an SKU's distribution. This presents a source for competitive advantage in markets driven by push–pull dynamics.